Peakbagging in the open cluster NGC 6819: Opening a treasure chest or Pandora's box?. Issue 8 (30th September 2016) - Handberg, R.; Miglio, A.; Brogaard, K.; Bossini, D.; Elsworth, Y. P.
Abstract: Here we report on an extensive peakbagging effort on the evolved red giant stars of the open cluster NGC 6819. This consists of around 50 stars spanning all the way up the red giant branch (RGB) and down to and including the red clump (RC). These stars represent a unique sample because of their common distance, metallicity and age. By employing sophisticated pre‐processing of the time series and Markov Chain Monte Carlo (MCMC) techniques, we have extracted individual frequencies, heights, and line widths for hundreds of individual oscillation modes in the sample of stars. We show that average asteroseismic parameters derived from these can be used to distinguish the stellar evolutionary state between RGB and RC stars without having to measure the often difficult dipole modes. Furthermore, we show how the fitting of some of these dipole modes can improve the detectability of acoustic glitches arising from the helium II ionization zone and how this can potentially be used to constrain the helium content in the cluster. We also discuss some of the difficulties facing similar studies in the future, where it seems that detailed studies of star clusters are facing some difficult times ahead.